In-between liberal authoritarianism and electoral authoritarianism: Hong Kong's democratization under Chinese sovereignty, 1997–2016. Issue 4 (7th June 2017) - Fong, Brian
ABSTRACT: On the eve of the twentieth anniversary of the handover, Hong Kong's transition towards a full democracy remains unsettled. Drawing upon the contemporary theories of hybrid regimes, this article argues that manipulations adopted by electoral authoritarian governments have become increasingly common in Hong Kong today. As Hong Kong's elections, opposition activities, and media have been increasingly put under electoral authoritarian-style manipulations, the city-state is now situated in the "political grey zone" in-between liberal authoritarianism and electoral authoritarianism and its transition into a full democracy remains nowhere in sight. The case study of Hong Kong will help enrich the existing comparative literature on hybrid regimes by developing a new "in-between category" and offering an interesting case of democratization of sub-national polity.